Candida glabrata Pneumonia in a Patient with Chronic Obstructive Pulmonary Disease. (2nd November 2016) - Yazici, Onur; Cortuk, Mustafa; Casim, Hasan; Cetinkaya, Erdogan; Mert, Ali; Benli, Ali Ramazan
Abstract : Pneumonia remains an important cause of morbidity and mortality among infectious diseases. Streptococcus pneumoniae and viruses are the most common cause of pneumonia. Candidiasis in such patients has been associated with haemodialysis, fungal colonization, exposure to broad-spectrum antibiotics, intensive care unit (ICU) hospitalization, and immunocompromised patients. The most common cause of infection is C. albicans . The case presented here is of a 66-year-old male patient diagnosed with C. glabrata . The patient suffered from chronic obstructive pulmonary disease.